Symmetrical Thalamic Lesions in the Newborn: A Case Series - Pols, T.; de Vries, L.S.; Salamon, A. Soltirovska; Nikkels, P.G.J.; Lichtenbelt, K.D.; Mulder-de Tollenaer, S.M.; van Wezel-Meijler, G. (Neuropediatrics, 2019)
Although bilateral injury to the thalami is often seen in (near)term infants with hypoxic ischemic encephalopathy (HIE), symmetrical thalamic lesions (STL) is a different, very rare condition, seen both in full-term and preterm infants often after an antenatal insult, although the history is not always clear. These lesions are usually first detected using cranial ultrasound (cUS). They may not always be seen on the first (admission) scan, but become apparent in the course of the 1st week after birth. Clinically, these infants present with hypo- or hypertonia, absence of sucking and swallowing reflexes, and they may have contractures and facial diplegia. Neuropathology commonly demonstrates a thalamic lesion with additional and variable involvement of basal ganglia and brainstem. The prognosis is very poor, the condition often leads to severe disabilities and/or death within the first years of life. The clinical course and neuroimaging findings of 13 patients with symmetrical thalamic lesions (STL) are reported.
Keywords: symmetrical thalamic lesions; newborn; neuroimaging